The Impact of Stress and Workload on Performance Moderated by Work Shift - Pangabean, Royhan Kamal; Junita, Audia; Miraza, Zuwina (Jurnal Administrasi Bisnis, 2024)
The objective of this research is to investigate the impact of stress and workload on the performance of PT Cheil Jedang Feed Medan's employees, moderated by work shifts. The study is explanatory and employs a quantitative approach. Primary data was collected by distributing questionnaires to a sample of 101 employees. The sample size was determined using the saturated sampling technique. The data was analyzed using multiple linear regression and moderation regression analysis. The study found that workload has a significant negative impact on employee performance, but work stress does not. Furthermore, the work shift variable has no significant moderating effect on the impact of stress and workload on employee performance at PT Cheil Jedang Feed Medan. Based on the results of this research, it turns out that these variables contribute minimally to employee performance. Practical suggestions that need to be perfected by PT Cheil Jedang Feed Medan are improvements in the aspect of the speed of rotation of working hours between employees and the provision of rest periods according to the relatively high level of stress and workload felt by employees